11. STUDIES ON ASPERGILLUS FLAVUS LINK AND ASPERGILLUS PARASITICUS SPEARE OF RADIX STEMONAE TUBEROSAE COLLECTED FROM THE TRADITIONAL MEDICINE STORES IN HANOI (Vietnam Journal of Community Medicine, 2024)
Objective: Analyzing fungi (A. flavus, A. parasiticus and the other species of Aspergillus) on Bach bo medicinal herb (Radix Stemonae Tuberosae) samples.Materials and methods: Using direct plating method based on morphological (colony & microbiological morphology) and biochemical characteristics on standard culture media: Barnett and Hunter’s genus level (1972); Raper and Fennell’s species level (genus Aspergillus) (1965); Samson, Hoekstra, Frivaad, Filtenborg (1995); Pitt and Hocking (2009).Results: From 10 herbal samples collected from traditional medicine stores in Lan Ong street (Hanoi), 93 fungal strains belonging to 5 species of Aspergillus Fr.: Fr. were isolated, including A. niger, A. flavus, A. parasiticus, A. tamarii, and A. aculeatus. Among them, 2 species A. flavus and A. parasiticus appeared respectively with higher RD and FQ indices of 25.8%; 60% and 11.8%; 50%, ranking 2nd and 3rd after A. niger (with RD = 37.6% and FQ = 60%).Conclusion: The results indicate presence of Aspergillus fungi in this medicinal herb source, especially 2 aflatoxin-producing species, posing a potential risk of carcinogenic toxins in Radix Stemonae Tuberosae samples. Thus, attention should be paid to harvesting, preserving, and processing this source material. The herbal material should be also tested for aflatoxin levels before use to ensure safety for consumers.
Keywords: Aspergillus; A. flavus; A. parasiticus; Radix Stemonae Tuberosae; Bach bo